Development and characterization of 24 microsatellite markers in Primula tosaensis, an endangered primrose, using MiSeq. Issue 1 (19th September 2017) - Yamamoto, Masaya; Handa, Yoshihiro; Aihara, Hiroki; Setoguchi, Hiroaki
Abstract: Primula tosaensis (Primulaceae) is an endangered primrose endemic to Japan. In this study, 24 novel microsatellite markers were developed using Illumina MiSeq sequencing to facilitate conservation of this endangered species. The genetic diversity and polymorphisms of these novel markers were measured in 32 individuals from a wild P. tosaensis population. The number of alleles and expected heterozygosities ranged from 2 to 5 (mean = 2.8) and from 0.119 to 0.724 (mean = 0.395), respectively. All loci were in Hardy–Weinberg equilibrium. The markers developed in this study will provide a powerful and practical tool for investigating the population structure and genetic diversity of P. tosaensis . Abstract : Primula tosaensis is an endangered species endemic to Japan. In this study, 24 novel microsatellite markers were developed using Illumina MiSeq sequencing to facilitate conservation of this endangered species. These markers will provide a powerful and practical tool for investigating the population structure and genetic diversity of this primrose.